2015
DOI: 10.1007/s10646-015-1521-x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and growth performance of the aquatic macrophyte Azolla filiculoides to sub-chronic exposure to cylindrospermopsin

Abstract: Physiological and biochemical effects of cylindrospermopsin (CYN), a cyanobacterial toxin that inhibits protein synthesis and released during a harmful cyanobacterial bloom, has been overlooked in plants. Therefore, at the present research, the toxic effects (physiological and biochemical) of a crude extract containing CYN were assessed in the aquatic fern Azolla filiculoides exposed to three concentrations (0.05, 0.5 and 5 μg CYN mL(-1)). At 5 μg CYN mL(-1), fern growth rate has showed a drastic decrease (0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 39 publications
(64 reference statements)
1
18
0
Order By: Relevance
“…However, in spite of the human health risks associated with CYN, less attention has been given to its bioaccumulation in edible agricultural plants compared with MCs [ 37 ], which is considered a public health concern, given CYN's high water-solubility and its ability to transfer to higher trophic levels [ 38 ]. This bioaccumulation may be possible because of the absorption of toxins by plants if surface water contaminated with cyanotoxins is used in agriculture, thus posing risks for food safety.…”
Section: Introductionmentioning
confidence: 99%
“…However, in spite of the human health risks associated with CYN, less attention has been given to its bioaccumulation in edible agricultural plants compared with MCs [ 37 ], which is considered a public health concern, given CYN's high water-solubility and its ability to transfer to higher trophic levels [ 38 ]. This bioaccumulation may be possible because of the absorption of toxins by plants if surface water contaminated with cyanotoxins is used in agriculture, thus posing risks for food safety.…”
Section: Introductionmentioning
confidence: 99%
“…Given the increased activity of the enzyme, GST, in strains of Microcystis , it is seems likely involved in the detoxification of ATX and MC-LR. Several studies have shown that GST is actively involved in the detoxification and biotransformation of cyanotoxins into molecules that are less toxic to the cell [11,14,16,17,18,26,51]. The detoxification and biotransformation of cyanotoxins in cells is carried out via a conjugation process that is catalyzed by GST using the reduced form of glutathione [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors hypothesize that the A. filiculoides could uptake and remove those cyanotoxins from the water. However, the fern did not uptake nor accumulate microcystins [81] and cylindrospermopsin [82], making this fern not suitable to the phytoremediation of those environmental contaminants.…”
Section: Phytoremediationmentioning
confidence: 95%